Dictionary of information science and technology - Khosrowpour, Mehdi, 1951- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"The 2nd edition of the Dictionary of Information Science and Technology is an updated compilation of the latest terms and definitions, along with reference citations, as they pertain to all aspects of the information and technology field"--Provided by publisher.